(untitled) (Politeja, 2020)
Discourses of Post-memory in Contemporary Transnational German Film The article is dedicated to the problem of trauma and death shown in contemporary transnational (made by directors living in Germany, but of non-German origin) German feature, documentary and experimental film. It raises the question of how the medium of film within its various narration and depiction modes (re)creates memory and post-memory, and at the same time it can be seen as a way to reclaim history in its personal or cultural dimension. The following films have been discussed: Totentraum (1995) and In fremder Erde (2001) by Ayhan Salar, Passing Drama (1999) by Angela Melitopoulos and The Cut (2014) by Fatih Akin. For this purpose, the author has implemented inter alia Aleida and Jan Assmann’s theory of memory.